Isolation and Characterization of CMCase Producing Bacteria for the Purpose of Converting Spent Mushroom Edible Canna Substrate into Organic Fertilizer - Nguyen, Phuong Anh; Truong, Thi Phuong; Tran, Lien Ha; Dang, Minh Hieu (JST: Engineering And Technology For Sustainable Development, 2021)
Converting spent mushroom substrates into organic fertilizer helps to tackle the problem of pollution in Edible canna starch processing villages and adds new value to the production chain of Edible canna. To successfully turn the spent substrates into compost, there is certainly an indispensable role for cellulolytic microorganisms, in which Bacillus strains are always important. Several bacterial strains have been isolated from spent Edible canna substrate after cultivation of monkey head mushroom in this study. Among isolated strains, the strain NDK5 has been selected exhibiting the highest cellulolytic activities with solubilization indexes of 6.14 and 18.3 mm for the ratio between the halo zone diameters and the colony diameters in the point cultivation method (SIratio) and the offset between the halo zone diameters and the agar hole diameters (SIoffset), respectively. The highest cellulase activity was 4.29 ± 0.071 U/ml. Morphological, physiological, biochemical, and 16S rRNA sequence analyses (100% homology with B. amyloliquefaciens sp. plantarum FZB42) were further carried out for the selected strain, leading to the identification of the strain as B. amyloliquefaciens sp. plantarum NDK5 strain. In addition, NDK5 was proved to have a capacity for synthesizing indole-3-acetic acid, a plant growth hormone, on an L-tryptophan-containing medium. Trial incubation of spent mushroom Edible canna-waste with the strain NDK5 showed increases in several quality criteria of the waste after 20 days of incubation, that meet the standard criteria for bio-organic fertilizer according to TCVN 7185:2002.